Theory of Applied Robotics Kinematics, Dynamics, and Control - Jazar, Reza N. (Springer US : Imprint: Springer, 2007)
Theory of Applied Robotics: Kinematics, Dynamics, and Control is appropriate for courses in robotics that emphasize kinematics, dynamics, and control. The contents of this book are presented at a theoretical-practical level. It explains robotics concepts in detail, concentrating on their practical use. Related theorems and formal proofs are provided, as are real-life applications. Students, researchers, and practicing engineers alike will appreciate this user-friendly presentation of a wealth of robotics topics, most notably orientation, velocity, and forward kinematics. Theory of Applied Robotics: Kinematics, Dynamics, and Control includes: Richly illustrated chapters and over 200 diagrams to help readers visualize concepts. More than 300 detailed examples with fully-worked solutions which expose readers to a balanced and broad understanding of robotics in today's world. A wealth of detailed problem sets and challenge problems for each chapter for the more advanced reader. A rich solutions manual which is available for instructors. Reza N. Jazar is an associate professor in the Mechanical Engineering Department at Manhattan College. His main research areas is nonlinear dynamic systems, including robotics, vehicles, and MEMS. He's written extensively on many diverse topics in applied mathematics and mechanical engineering subjects. He regularly teaches undergraduate and graduate-level courses on mechanical engineering.